2011
DOI: 10.1155/2011/538671
|View full text |Cite
|
Sign up to set email alerts
|

The In Vivo Antidiabetic Activity of Nigella sativa Is Mediatedthrough Activation of the AMPK Pathway and Increased Muscle Glut4Content

Abstract: The antidiabetic effect of N. sativa seed ethanol extract (NSE) was assessed in Meriones shawi after development of diabetes. Meriones shawi were divided randomly into four groups: normal control, diabetic control, diabetic treated with NSE (2 g eq plant/kg) or with metformin (300 mg/kg) positive control, both administered by daily intragastric gavage for 4 weeks. Glycaemia and body weight were evaluated weekly. At study's end, an Oral Glucose Tolerance Test (OGTT) was performed to estimate insulin sensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
58
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 39 publications
3
58
0
1
Order By: Relevance
“…NSE animals showed a progressive normalization of glycaemia. It was also demonstrate that in vivo treatment with NSE exerts an insulin-sensitizing action by enhancing ACC phosphorylation, a major component of the insulinindependent AMPK signaling pathway, and by enhancing muscle Glut4 content [54] .…”
Section: Antidiabetic Activitymentioning
confidence: 86%
“…NSE animals showed a progressive normalization of glycaemia. It was also demonstrate that in vivo treatment with NSE exerts an insulin-sensitizing action by enhancing ACC phosphorylation, a major component of the insulinindependent AMPK signaling pathway, and by enhancing muscle Glut4 content [54] .…”
Section: Antidiabetic Activitymentioning
confidence: 86%
“…In normal mammalian cells, MG is efficiently detoxified via the glutathione-dependent glyoxalase pathway, which involves the enzymes glyoxalase 1(Glo-1) and glyoxalase 2 Xu et al, 2013;Zeng et al, 2013). Under conditions of hyperglycemia and impaired glucose metabolism, MG often accumulates (Benhaddou-Andaloussi et al, 2011). Abundant MG levels induce dysfunction in mitochondrial respiration (Luiken et al, 2008) and increased production of reactive oxygen species (ROS) (Wijesekara et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The N. sativa seed ethanol extract could also inhibit gluconeogenesis by the liver and muscle activation of adenosine monophosphate-activated protein kinase (AMPK)(Benhaddou-Andaloussi et al, 2011). It was demonstrated that TQ (the main constituent of N. sativa) could reduce the expression of gluconeogenic enzymes (glucose-6-phosphatase and fructose 1, 6 bisphosphatase) and hepatic glucose production(Al-Rasheed et al, 2014;Alimohammadi et al, 2013).…”
mentioning
confidence: 99%